2006
DOI: 10.1615/critrevimmunol.v26.i6.50
|View full text |Cite
|
Sign up to set email alerts
|

DNA Motifs Suppressing TLR9 Responses

Abstract: Immune cells respond to bacterial DNA containing unmethylated CpG motifs via Toll-like receptor 9 (TLR9). Given the apparent role of TLR9 in development of systemic lupus erythematosus (SLE), there is interest in the development of TLR9 inhibitors. TLR9-mediated responses are reported to be inhibited by a confusing variety of different DNA sequences and structures. To aid characterization, we have provisionally categorized TLR9-inhibitory oligodeoxynucleotides (ODN) into 4 classes, on the basis of sequence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…Similarly, IFN-α production by human PBMCs in response to our DNA-IC were reduced in the presence of antagonistic ODN (Figure S1D) or chloroquine (Figure S1E), both of which inhibit TLR9 activation (Trieu et al, 2006; Macfarlane and Manzel, 1998). We further investigated our model of in vitro formed DNA-IC in fetal liver-derived murine pDCs, a cell type that in our knowledge has not previously been used to investigate TLR9 responses and that was used throughout the current study.…”
Section: Resultsmentioning
confidence: 82%
“…Similarly, IFN-α production by human PBMCs in response to our DNA-IC were reduced in the presence of antagonistic ODN (Figure S1D) or chloroquine (Figure S1E), both of which inhibit TLR9 activation (Trieu et al, 2006; Macfarlane and Manzel, 1998). We further investigated our model of in vitro formed DNA-IC in fetal liver-derived murine pDCs, a cell type that in our knowledge has not previously been used to investigate TLR9 responses and that was used throughout the current study.…”
Section: Resultsmentioning
confidence: 82%
“…In keeping with A151’s effects on TLR9 activation conversion to a phosphodiester backbone (PD) completely abolished A151-mediated inhibition of IFI16 and AIM2 at the concentrations tested (41). Sequence also proved to be important; substitution of A151’s guanosine triplet with adenosine residues reduced construct potency by 94%.…”
Section: Discussionmentioning
confidence: 86%
“…To further confirm the participation of TLR7/9 in apoptotic MMP-mediated pDC activation, MMP stimulation was carried out in the presence of the G-rich inhibitory ODN (iODN) PZ3, which was previously shown to interfere with TLR9 activity (46,47). The results obtained showed that PZ3 blocks MMP-induced IFN-a production, although IFN induction with the synthetic TLR7 ligand R848 was unaffected (Fig.…”
Section: Endocytotic Uptake Of Mmp Is a Prerequisite For Pdc Activationmentioning
confidence: 81%